Geological problem solving with LOTUS 1-2-3 for exploration and mining geology (with programs on diskette) - Koch, George S.; ScienceDirect eBooks (Oxford ; New York : Pergamon Press, 1990)
Presents effective methods for using Lotus 1-2-3 techniques to solve problems in exploration and mining geology. 1-2-3 programmes are provided in conjunction with named worksheets or templates, together with brief explanatory text. Problem solving is based on a well-established and maintained software package. A floppy diskette is supplied enabling users, following brief instructions, to solve problems immediately.
Includes bibliographical references (pages 201-204) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Elsevier
Keywords: Lotus 1-2-3 (Computer file); Lotus 1-2-3 (Computer file); Prospecting -- Statistical methods -- Data processing; Mining geology -- Statistical methods -- Data processing; TECHNOLOGY & ENGINEERING -- Mining; Electronic books